2001
DOI: 10.1007/s004240000449
|View full text |Cite
|
Sign up to set email alerts
|

Tissue distribution and functional expression of the human voltage-gated sodium channel β3 subunit

Abstract: This study investigated the distribution of beta3 in human tissues and the functional effects of the human beta3 subunit on the gating properties of brain and skeletal muscle alpha subunits. Using RT-PCR of human cDNA panels, beta3 message was detected in brain, heart, kidney, lung, pancreas and skeletal muscle. Both alphaIIA and SkM1 expressed in Xenopus oocytes inactivated with a time course described by two exponential components representing fast and slow gating modes, while co-expression of human beta3 wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2001
2001
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 40 publications
(59 reference statements)
0
17
0
Order By: Relevance
“…An additional subunit, ␤ 3 , predominant during development (406), has been found that accelerates inactivation but less than ␤ 1 with which it is closely related (300). The distribution of ␤ 3 in human tissues and comparative amino acid sequences of ␤ 1 , ␤ 2 , and ␤ 3 is described in Stevens et al (426). Most recently, a novel disulfide-linked subunit, ␤ 4 , has been identified which shows similarities with ␤ 2 ; on coexpression it shifts the activation curve in the hyperpolarizing direction without affecting inactivation (516).…”
Section: Importance Of the ␤-Subunitsmentioning
confidence: 94%
“…An additional subunit, ␤ 3 , predominant during development (406), has been found that accelerates inactivation but less than ␤ 1 with which it is closely related (300). The distribution of ␤ 3 in human tissues and comparative amino acid sequences of ␤ 1 , ␤ 2 , and ␤ 3 is described in Stevens et al (426). Most recently, a novel disulfide-linked subunit, ␤ 4 , has been identified which shows similarities with ␤ 2 ; on coexpression it shifts the activation curve in the hyperpolarizing direction without affecting inactivation (516).…”
Section: Importance Of the ␤-Subunitsmentioning
confidence: 94%
“…The protein, Na v b3, is composed of an N-terminal extracellular Ig-like domain, a transmembrane domain and a C-terminal intracellular domain. Na v b3 is expressed in the brain, heart, lung, skeletal muscle, kidney, and pancreas [Stevens et al, 2001]. The SCN3B gene is a member of the gene family SCNB gene family [Meadows and Isom, 2005] described above under SCN1B.…”
Section: Brs7-mutations In Scn3bmentioning
confidence: 99%
“…b1 and b3 are co-expressed in many tissues [17,18]. In the heart, b1 is expressed throughout both atria and ventricles, whereas b3 expression is limited to the ventricles and Purkinje fibers [9].…”
Section: Introductionmentioning
confidence: 99%